2016
DOI: 10.1590/0004-282x20160037
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular migraine: diagnosis challenges and need for targeted treatment

Abstract: Approximately 1% of the general population suffers from vestibular migraine. Despite the recently published diagnostic criteria, it is still underdiagnosed condition. The exact neural mechanisms of vestibular migraine are still unclear, but the variability of symptoms and clinical findings both during and between attacks suggests an important interaction between trigeminal and vestibular systems. Vestibular migraine often begins several years after typical migraine and has a variable clinical presentation. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 55 publications
1
4
0
7
Order By: Relevance
“…VM is a distinct clinical entity that accounts for a high proportion of vestibular symptoms.Diagnosis of VM mainly dependson recurrent vestibular symptoms, ahistory of migraine, a temporal association between vestibular symptoms and migraine symptoms and exclusion of other reasons [2].And vestibular symptoms is based on the bárány society's classi cation of vestibular symptoms such as spontaneous vertigo, positional vertigo, visually-induced vertigo,head motion-induced vertigo and head motion-induced dizziness with nausea [15].In our studies, more than half of VM patientsare found spontaneous vertigo.10-20%VM patients have other forms of vertigo. We can nd thatthe most common vestibular symptom is spontaneous vertigo.Findings of most of studiesare similar our results [1,16,17]. Although most of VM patients have moderate to severevestibular symptoms.We still found some mild VM patients.…”
Section: Discussionsupporting
confidence: 88%
“…VM is a distinct clinical entity that accounts for a high proportion of vestibular symptoms.Diagnosis of VM mainly dependson recurrent vestibular symptoms, ahistory of migraine, a temporal association between vestibular symptoms and migraine symptoms and exclusion of other reasons [2].And vestibular symptoms is based on the bárány society's classi cation of vestibular symptoms such as spontaneous vertigo, positional vertigo, visually-induced vertigo,head motion-induced vertigo and head motion-induced dizziness with nausea [15].In our studies, more than half of VM patientsare found spontaneous vertigo.10-20%VM patients have other forms of vertigo. We can nd thatthe most common vestibular symptom is spontaneous vertigo.Findings of most of studiesare similar our results [1,16,17]. Although most of VM patients have moderate to severevestibular symptoms.We still found some mild VM patients.…”
Section: Discussionsupporting
confidence: 88%
“…The World Health Organization ranks migraine as the third most costly neurological disorder (1,2). Since there is no specific test to diagnose migraine, diagnosis is based on clinical history (3). This pain syndrome is associated with nausea and/or vomiting, photophobia and phonophobia (4).…”
Section: Introductionmentioning
confidence: 99%
“…During the acute attacks of vertigo, the analysis of the positional nystagmus usually permits differentiation of positional VM from benign paroxysmal vertigo. [13] TIA is considered more frequently in later ages. Ischemic attack is different to VM, with other accompanying neurological findings, risk factors, and a pathological doppler ultrasonography.…”
Section: Discussionmentioning
confidence: 99%